Produção de textos multimodais no suporte digital por crianças de 8 a 10 anos provenientes de duas escolas públicas - Rodrigo Vieira Rezende (2021)
The general objective of this research was to investigate the production of multimodal texts on digital devices and the use of semiotic modes and resources by children aged 8 to 10 from two public schools in Belo Horizonte/MG - Brazil. The research was guided by some key questions: how do children who are students at a municipal public school in Belo Horizonte/MG use and mobilize different semiotic resources for the construction of meanings in the production of multimodal texts in their social practice and in the activities proposed in this search? What is the importance of the written mode in the production of multimodal texts by those children? To answer them, we sought to: a) Identify and analyze the social practices of textual production with the use of digital technologies experienced by children and other multimodal practices; b) Analyze how children use semiotic modes and resources in the production of proposed texts; and c) Identify and analyze how children mobilize the semiotic written mode in relation to other modes in the production of proposed multimodal texts. The investigation dialogues with studies on digital written culture, a term that refers to material and symbolic aspects and the uses of reading and writing practices in digital support (FRADE; ARAÚJO; GLÓRIA, 2018), with the assumptions of literacy as a social practice (STREET, 2014a), with studies on multimodality based on the idea that texts are always seen as multimodal (KRESS; BEZEMER, 2009) and with studies by Jewitt (2005), who argues that writing on screens forms complex multimodal sets of image, sound, animation and other modes of representation and communication. The investigation was based on the qualitative approach of research in the field of education and the entire data collection was carried out during the Covid-19 pandemic situation. Online interviews were conducted with 20 children and 7 parents to learn about their digital practices and the participants produced suggested handwritten and digital texts. The production process of digital multimodal texts was monitored online in real time during the research. The main results indicate that 90% of children produce multimodal texts, mainly through social media platforms; they have wide access to digital devices, with 80% of them owning their own smartphone device. However, this considerable digital access is not automatically converted into full text production processes, with limiting factors such as: low access to different digital devices and/or devices shared with family members; poor quality of digital devices limiting the use of various semiotic resources; the social control exercised by parents who point out fears about the risks of online activities. Despite this, it was demonstrated that the investigated children were very willing to experiment and integrate various semiotic modes, such as static and moving images and sounds. The written mode occupies a prominent place in productions, in general. Although the materiality of the digital support has a great influence, the process of production of multimodal texts by children is also crossed by other factors such as thematic/content; the textual type and genre; the recipient; the influences of digital platforms shaping such a process; digital literacy and representations and values about written culture and the social value of writing. The production of multimodal texts on digital support has enabled participation in real and non-artificial communicative practices, an expansion of the capacity for expression and an increase in children's opportunities for action in the world.